(untitled) (Research, Society and Development, 2022)
Traumatic brain injury (TBI) is configured as a problem in the field of public health, in view of its incidence and consequent injuries. In addition to physical damage, brain injuries are harmful in terms of the main cognitive functions, namely: memory, executive functions, attention and language. Objective: to characterize the epidemiological profile of TBI cases in the northern region of the state of Ceará and, from that, to identify the prevalence of types and locations of lesions. Methodology: from a documentary research, epidemiological data were collected over the last six years, that is, 2015-2020, from a documental research in medical records, carried out at the trauma reference hospital complex in the northern region of Ceará: Santa Casa Misericórdia de Sobral. Results: Of the 366 medical records analyzed, 284 patients were discharged from the hospital (78%) and 27 were other reasons for leaving the institution, such as evasion and transfer to another hospital (7%). The first group was considered the survivors, while the second made it impossible to record such information. In addition, traffic accidents were the main cause of TBI with a predominance of damage to the frontal and temporal lobes, located in the prefrontal cortex, with impairment in executive functions. Conclusion: The present study aimed to build an updated epidemiology of the prevalence of Traumatic Brain Injury in the northern region of Ceará, in order to discuss the results in the light of the current literature on the subject, focusing on possible neuropsychological sequelae.